The New Digital Flesh of Fantastic Bodies. - Mellier, Denis (Substance: A Review of Theory & Literary Criticism, 2018)
From the fantastic inscribed on bodies, frightening as well as suffering bodies, and cinematic technologies inventing new spectacular forms of these bodies, a history of the one based on the formal possibilities of the other could well be imagined. We can thus explore cinema through the mutations of the body inherent to the fantastic. Considering the transparencies and superpositions of the silver era of cinema, the cuts and assemblies of the editing process, all the way to contemporary digital bodies, we can ask whether it is a question of a simple continuity, a renewal of the same discourse on the body, its mutations and alterations that it is going along its visual improvements. Or shouldn't we rather see that the digital is opening up different perspectives as the body has been acquiring an authentic digital skin in recent fantastic cinema. Cartoonization of the body, plasticity, endoscopic journeys into bodies and matter, extreme mobility, changes of scale, liquidity and disintegration are symptoms of the anxieties and phantasms attached to the body in the era of the digital fantastic.